TÓPICOS SOBRE SENSUALIDADE, SEXUALIDADE E EMANCIPAÇÃO: UM SURVEY SOBRE AS MULHERES NEGRAS. - Andréia Soares Pinto; Isabel Cristina Fonseca da Cruz (Universidade Federal de Goias, 2001)
African-brazilian women have been excluded from society and research projects. This study points out the social inequality survey in Rio de Janeiro and its impact on the health status of African-brazilian woman. A survey was conducted with a population of 1.172 people and the 297 (25.3%) women compound the sample. The results revealed that 46.5% are unsatisfied with her own appearance; the majority is married, has less than a high school degree, has an income inferior than R$ 151 (US$ 75,5). We concluded that the lower socioeconomic status has its roots on racial discrimination which is a chronic and persistent stressor to the health of African-brazilian women. We suggest the further research on the responses of African-women to the health problems could help clarify the racism as a etiologic factor of many conditions.